PERMODALAN, EFISIENSI, RISIKO KREDIT DAN LIKUIDITAS BANK PERKREDITAN RAKYAT (BPR) DI JAWA BARAT: APLIKASI REGRESI KUANTIL BOOTSTRAP - Farah Latifah Nurfauziah (Universitas Katolik Indonesia Atma Jaya, 2020)
This study investigated the internal factors of West Java the Rural Commercial Bank’s (Bank Perkreditan Rakyat) capital adequacy on yearly data of 64 BPRs from 2014 to 2018. The results reveal several main drivers of capital adequacy ratio BPR’s in West Java. Data was collected from secondary data and data analysis using quintile regression with a bootstrapping technique. We found that the ratio of operating expenses to operating income (BOPO) affects capital adequacy ratio negatively, meanwhile, return on assets (ROA) and loan to deposit ratio (LDR) affect capital adequacy ratio positively. The other result proved that the operating expenses to operating income (BOPO) have a negative effect on return on assets (ROA), meanwhile, the loan to deposit ratio (LDR) and current ratio (CR) has a positive effect on return on assets (ROA), respectively. It is recommended that empirical studies should be undertaken in the same field to find out what more internal factors could affect BPR’s capital adequacy